Engineering Simulation Model of Paralel Type Heat Exchanger in Tomato Juice Pasteurization - Komar, Nur (Jurnal Teknologi Pertanian, 2010)
Heat exchanger for pasteurization model was developed by making energy balance based on volume control. The model was solved with numerical method and the exact solution as the value of comparison of numerical methods. The distribution of variable temperature (T) at specific points along the pipeline both in the heating pipe (the pipe to be heated) was determined.  N1 = (U0. .D0/mh.Cph) was used as heaters constants, N2 = (Ui. .Di/mc.Cpc) as fluid flow parallel to the juice, and M1 = (Ui. .Di/mc.Cpc) as fruit juice constant heating. All equations were then solved by Runge Kutta 4th order equation which is commonly used in the engineering analysis. Runge Kutta equations that have a variation of the error ( x)4 can be use equation  Ti + 1 = Ti + (K1 + 2K2 + 2 K3 + K4)/6.  The value of Ti+1 was the temperature at one point to i+1, while Ti was the temperature of the previous point (i).  Tests were conducted in parallel simulation program menu with the following data: Cp = 4.18 kJ/kg C, Cp fruit juice = 4.007 kJ/kg C, hh = 0.1597 W/m2 C, mk = 0.023 kg/s, Do = 0023 m, mc = 0016 kgs, hc = 0.1575 W/m2 C,  Di = 0.02 m, L = 4 m, dx = 0.2, x0 = 0, TH0 = 100 C, Tc0 = 20 C.  The result showed that the value of M1 was 0.154355 and N2 was 0.58802, which remained the big distribution of temperature that would provide a rapid rise and constant. The value of N1 = 0.198792 was fixed with a smaller value that obtained by rapidly rising temperature distribution and constant at N2. In contrast, N1 or N2 value was very small to reduce the heat and the fluid flow rate constant value would be longer achieved.Keywords: heat exchanger, pasteurization model, volume control